Essentials of organizational behavior - Robbins, Stephen P. 1943- (Prentice Hall, 2003)
This book features only the most relevant topics in organizational behavior today, such as TQM; reengineering, technology; empowerment; declining employee loyalty; the Myers-Briggs Type Indicator; virtual and boundaryless organizations; 360-degree performance appraisals; diversity; globalization; ethics; and more. Lively and informative, this masterfully crafted introduction condenses the essentials of the field into a tightly focused presentation. A four-part organization covers an introduction to organizational behavior, the individual in the organization, groups in the organization, and the organization system. For directors of human resource and other individuals in a variety of managerial positions.